2004
DOI: 10.1063/1.1666976
|View full text |Cite
|
Sign up to set email alerts
|

Influence of thickness and dielectric properties on implantation efficacy in plasma immersion ion implantation of insulators

Abstract: Passivation layer on polyimide deposited by combined plasma immersion ion implantation and deposition and cathodic vacuum arc techniqueEffects of mesh-assisted carbon plasma immersion ion implantation on the surface properties of insulating silicon carbide ceramics Plasma immersion ion implantation of insulators is an interesting topic both theoretically and industrially. The net energy of the incident ions is dictated by the surface potential and for conductors is equal to the voltage applied to the backside … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…In plasma immersed ion implantation (PIII) sudden negative bias pulses are applied to a surface such that positive ions are implanted in the material [19]. Several authors have seen that implanting into a dielectric substrate results in a significant voltage build-up in the wafer, reducing the effective implant energy [20,21]. In our case, a film composed of fluorine and sulfur can deposit on the acceleration grids.…”
Section: First Laboratory Tests In Pegases IImentioning
confidence: 95%
See 1 more Smart Citation
“…In plasma immersed ion implantation (PIII) sudden negative bias pulses are applied to a surface such that positive ions are implanted in the material [19]. Several authors have seen that implanting into a dielectric substrate results in a significant voltage build-up in the wafer, reducing the effective implant energy [20,21]. In our case, a film composed of fluorine and sulfur can deposit on the acceleration grids.…”
Section: First Laboratory Tests In Pegases IImentioning
confidence: 95%
“…This film is also detectable by measuring a decrease in the current on the grids. In the presence of a dielectric layer on the plasma grid, a certain voltage will be dropped in the dielectric such that the effective acceleration voltage is [21] V where δ is the thickness of the dielectric film and Q is the surface charge. For a quick estimate using δ ∼ 1 µm, Q ∼ 1 × 10 16 and ε r = 3.7 as for pure sulfur, the voltage drop in the dielectric is about 50 V, which is of the order of the measured energy loss for negative ions.…”
Section: First Laboratory Tests In Pegases IImentioning
confidence: 99%
“…If the pulse length is long enough and/or the plasma density high enough, the insulator will charge up to the floating potential where the flux of electrons and ions to the surface is equal [8]. To minimize surface charging and improve the depth of treatment, a metal mesh can be placed around the insulator and pulse biased together with the object [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…To date, there have been limited experimental studies of the effects of surface charging on the IED during PIII of insulators. Experimental studies have investigated the effects of the use of metal grids and the thickness and dielectric constant of the insulator on the implantation depth of ions [9,10]. The effects of an insulator on IEDs at dc and radio frequency (RF) biased substrates have been studied using computer simulation [23,24] and have shown that near a metal/insulator interface the ion flux and energy distribution are significantly affected by sheath distortion.…”
Section: Introductionmentioning
confidence: 99%